Timescales of the Climate Record in the South Polar Ice Cap of Mars - Becerra Valdes, Patricio; Sori, Michael M.; Thomas, Nicolas; Pommerol, Antoine; Simioni, Emanuele; Sutton, Sarah S.; Tulyakov, Stepan; Cremonese, Gabriele (Geophysical Research Letters, 2019)
The South Polar Layered Deposits (SPLD) are the largest water ice reservoirs on Mars. Their accumulation is believed to result from climate oscillations that drive the movement of ice and dust on the surface. The High‐Resolution Imaging Science Experiment and the Colour and Stereo Surface Imaging System have imaged exposures of its internal structure in troughs and marginal scarps. Here we use the stereo imaging products of these instruments to extract stratigraphic proﬁles representative of various locations throughout the SPLD. Through wavelet and series‐matching analyses of these proﬁles, we reveal periodicities in the stratigraphy that correlate to the orbital oscillations that drive climate change on Mars and that have been observed to force the accumulation of the north polar cap. We infer that the water ice and dust of the SPLD were deposited at variable rates of 0.13–0.39 mm/year, taking a minimum of 10–30 Myr to accumulate.